PERAN PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN MORAL SISWA DI LINGKUNGAN SEKOLAH MULTIKULTURAL: STUDI PADA SMP NEGERI 15 KOTA BENGKULU - Dalima Septiria; Dian Jelita; Novita Rahmayanti; Shelda Tenri Bela; Siti Zulaiha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study explores the role of Islamic Religious Education (PAI) in strengthening students’ moral development within a multicultural school environment at SMP Negeri 15 Bengkulu City. The research aims to analyze the moral issues faced by students, describe PAI-based moral development strategies, and identify supporting and inhibiting factors in their implementation. Using a qualitative descriptive method, data were collected through interviews, observations, and documentation. The findings reveal that PAI contributes significantly to students’ moral formation through dialogical learning, contextual material delivery, teacher role modelling, and structured religious programs such as congregational prayer and daily worship habits. A multicultural environment also enhances students’ tolerance and respect for diversity. However, several challenges remain, particularly digital behavior, cultural differences, and limited parental involvement. Overall, PAI demonstrates a strategic role in fostering moral awareness, discipline, and social harmony among students.